No-Needle Jet Intradermal Aminolevulinic Acid Photodynamic Therapy for Recurrent Nodular Basal Cell Carcinoma of the Nose: A Case Report - Daniel Barolet; Annie Boucher (Journal of Skin Cancer)
Photodynamic therapy (PDT) with aminolevulinic acid (ALA) to treat nodular basal cell carcinoma (BCC) has been shown to be beneficial. The success rate of ALA-PDT in the treatment of nodular BCC is dependent on optimal penetration of the photosensitizing agent and subsequent PpIX production. To enhance topical delivery of drugs intradermally, a needleless jet injection (NLJI), which employs a high-speed jet to puncture the skin without the side effects of needles, was used in one patient with recurrent BCC of the nose. Photoactivation was then performed using red light emitting diode [CW @ λ 630 nm, irradiance 50 mW/cm2, total fluence 51 J/cm2] for 17 minutes. Excellent cosmesis was obtained. Aside from mild crusting present for six days, no other adverse signs were noted. Clinically, there was no recurrent lesion up two years postintervention. Additional studies in larger samples of subjects are needed to further evaluate this promising technique.